EMISIÓN DIFUSA DE DIÓXIDO DE CARBONO Y VAPOR DE MERCURIO EN EL VOLCÁN MIRAVALLES, COSTA RICA - Melián, Gladys V. (2011)
The purpose of this study is to evaluate the spatial distribution of diffuse CO2 and elemental Hgdegassing at Miravalles volcano as well as to estimate the total output CO2 efflux. Relatively high soil CO2 effluxmeasurements and soil vapor Hg0 concentrations were observed at Miravalles, reaching values up to 24 kg m-2d-1, and 25 ppbV, respectively. Anomalous soil CO2 efflux, soil vapor Hg0 values and relatively heavy carbonisotopic signatures of carbon for the soil gas CO2 were spatially well correlated with major volcano-structuralcharacteristics of Miravalles. Diffuse CO2 degassing rate of the study area yields 12 700 t d–1. These results areuseful to improve the geochemical monitoring program for the volcanic surveillance of Miravalles.